Adsorption of cadmium and zinc onto Stenochlaena palustris (Paku Midin) : potential agent for removal or recovery in aqueous solutions - Hashim, Mohd Akmal (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2008)
The ability of Stenochlaena palustris (Paku Midin) to remove Cadmium and Zinc from aqueous solution by adsorption was studied. The effects of Contact Time, pH and temperature of the solution, initial metal concentration prior to loading, presents of other metal ions, and adsorbent size/dose were studied in batch experiments . For this study, the weight and size of the adsorbent material were fixed. The weight of the adsorbent material used were set at 0.5 gram and size of#l20 based on the use Screen sieves. The initial metal concentration are also been fixed at I ppm and 2ppm for Zinc and Cadmium respectively. The results have shown that the leaves of Paku Midin can adsorp Cadmium up to 86.83 percent at 75 minutes contact time, while the stems can adsorp 83.36 percent at 30 minutes. After 30 and 75 minutes, the adsorption capacity of the adsorbent has shown reduction value, which indicate that 30 minutes and 75 minutes are the optimum contact time for Paku Midin stems and leaves respectively. However, the adsorbent was uneffective against Zinc adsorption or in other words the adsorbent cannot adsorp Zinc from the aqueous solution that have been prepared. For pH effect analysis, the leaves seems to show higher capacity of Cadmium adsorption at acidic or basic pH conditions, but less effective in near neutral pH condition. As for the stem of Paku Midin, adsorption of Cadmium seems to be better at pH below and above 5. For temperature study, the results has shown that both Paku Midin stems and leaves are more effective at higher temperature condition .